A Numerical Method for Blast Shock Wave Analysis of Missile Launch from Aircraft - Sebastian Heimbs; Josef Ritzer; Johannes Markmiller (International Journal of Aerospace Engineering)
An efficient empirical approach was developed to accurately represent the blast shock wave loading resulting from the launch of a missile from a military aircraft to be used in numerical analyses. Based on experimental test series of missile launches in laboratory environment and from a helicopter, equations were derived to predict the time- and position-dependent overpressure. The method was finally applied and validated in a structural analysis of a helicopter tail boom under missile launch shock wave loading.